Do flexible repayment schedules improve the impact of microcredit? Evidence from a randomized evaluation in rural India - Kristina Czura (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
Microcredit institutions typically apply rigid and fixed repayment schedules when disbursing loans in order to reduce transaction costs, simplify procedures, and inculcate fiscal discipline for better repayment behavior. Microcredit clients, however, often have neither smooth income nor singular moments in which to make lumpy investments throughout the year. This mismatch generates a cash flow disconnect and, given the presumed liquidity constraints of the typical microcredit client, a potential welfare loss. Using data from a randomized evaluation with dairy farmers in rural India, we test the impact of flexible microcredit repayment schedules relative to "normal" inflexible, fixed repayment schedules. Although we are only able to track those who borrow, which introduces potential selection effects, we find amongst those in flexible lending groups some evidence for higher ability to absorb shocks and higher income, which seems to be driven by limited improvements in investment and higher production from milk. On the cost-side, defaults do increase for the lender. Towards the end of the study, the microcredit market encountered crisis, with mass defaults, thus it is hard to generalize with respect to the default results. We conclude with caution, that we have shown suggestive evidence that a more flexible product design, one tailored to the needs of a dairy farmer, may be welfare enhancing for the dairy farmer. Further work is needed to both validate these results, and explore how to balance any trade-off with default.
urn:nbn:de:bvb:19-epub-26608-7
Keywords: O16; Q14; 330; Flexible repayment schedules; microfinance; microcredit; consumption smoothing